THE RELATIONSHIP BETWEEN SCENT MARKETING AND PURCHASE INTENTION: THE CASE OF STARBUCKS CONSUMER OF METRO MANILA - Latina, Nicole Anne; Sordan, Fatima Hannah; Calamba, Lanz Jerome; De Jesus, Francis Lawrence (International Journal of Social and Management Studies, 2022)
It has come to our attention that there is a strategic niche in marketing, which is taking advantage of the olfactory stimuli in the market. The food industry is known for using scent marketing as a technique to attract consumers. This industry employs this strategy in the form of developing unique ambient scents that consumers will fondly recall. Moreover, this paper discusses more on the effects of how the food industry takes advantage of the olfactory stimuli of the market and how it increases the consumers’ willingness to purchase the product. A combination of questionnaires with randomly selected Starbucks consumers will give answers to the objectives of this study. The findings of this study will be a significant contribution not only to the food industry but also to the consumer behavior literature, incorporating the most up-to-date research and concentrating on all key thematic topics connected to scent and purchase intention. The study discovered the following findings: Although the respondents already had a high purchasing intention to the coffee chain, it was revealed that brand recall had little effect on purchase intent. In contrast, emotions had the highest impact on purchase intent. This implies that for each unit increase in emotion, expected purchasing intention increases by 0.333, and for desire, it increases by 0.189.